Jenis-Jenis Ikan Hasil Tangkapan Nelayan dengan Alat Tangkap Seine Net di Pesisir Desa Sanggalangit, Kabupaten Buleleng, Bali - Cahyani, Putri Eka; Arthana, I Wayan; Wijayanti, Ni Putu Putri; Wirawan, I Gede Wahyu Surya (Current Trends in Aquatic Science; Vol 4 No 1 (2021), 2021)
Sanggalangit Village is one of the villages in Gerokgak District, Buleleng Regency with the main potential of anchovy fisheries and several other types of fish. The fishing gear used is dominated by seine net. The purpose of this research is to determine the types of fish that have landed to assist in sustainable fisheries management. This research took time from December 2019 to January 2020. Fish samples were obtained by direct observation in the field. Fish sampling was taken using simple random sampling. The catch of fishermen with seine net fishing gear found 23 species of fish grouped into 8 orders and 16 families. The type of fish wealth index obtained was 2.,07, categorized as a low type of wealth index. The relative abundance of fish species received quite a variety of values ranging from 0,01%-0,15%. The analysis of the relationship between the length and weight of the main catch fish showed that the growth patterns were negative allometric.